2022
DOI: 10.3390/ma15217703
|View full text |Cite
|
Sign up to set email alerts
|

Silica and Silica-Based Materials for Biotechnology, Polymer Composites, and Environmental Protection

Abstract: Over recent years, silica and silica-based materials have become some of the most frequently used materials worldwide [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The discovery of silica-based nanostructured materials opened new perspectives for the development of new materials with organized structures containing heteroatoms [ 1 , 2 ]. Due to the high surface area and accessibility of their pore systems, these materials have been promising as acid catalysts in petrochemical processes [ 3 , 4 , 5 ], supports for heteropolyacids [ 6 , 7 , 8 ], liquid phase catalysis [ 9 , 10 , 11 ], and in advanced materials technology [ 12 , 13 , 14 , 15 , 16 , 17 ]. Due to the great interest in these materials, it is necessary to develop new methodologies for synthesis, post-synthesis treatments, in addition to new characterization methods.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of silica-based nanostructured materials opened new perspectives for the development of new materials with organized structures containing heteroatoms [ 1 , 2 ]. Due to the high surface area and accessibility of their pore systems, these materials have been promising as acid catalysts in petrochemical processes [ 3 , 4 , 5 ], supports for heteropolyacids [ 6 , 7 , 8 ], liquid phase catalysis [ 9 , 10 , 11 ], and in advanced materials technology [ 12 , 13 , 14 , 15 , 16 , 17 ]. Due to the great interest in these materials, it is necessary to develop new methodologies for synthesis, post-synthesis treatments, in addition to new characterization methods.…”
Section: Introductionmentioning
confidence: 99%
“…Fused silica [ 8 , 9 , 10 , 11 ] was a common candidate for ceramic cores, by virtue of its low thermal expansion coefficient (0.55 × 10 −6 /K between 25 °C and 1000 °C), low sintering temperatures, chemical stability against superalloy liquids and superior leachability in aqueous alkali; it was reported that 90% of the present ceramic cores were silica-based [ 1 ]. However, the resistance to high-temperature deformation required improvement, due to the low viscosity of silica glass at high temperatures.…”
Section: Introductionmentioning
confidence: 99%